Financial profitability analysis of dairy milk production in some selected areas of Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2022)
The study analyzed profitability and productivity of dairy milk production from a survey of 70 respondents (farmers and market actors) in Dhaka region. Responsible factors that affect dairy milk production were identified using the Cobb-Douglas production function. The findings unveil that significant coefficients of variables exhibit positive impact on the dairy milk production. It is possible for dairy farmers to enjoy sufficient profits from milk production since earned gross return and net return were Tk. 1099 and Tk. 594, respectively against the total cost of production Tk. 487.83 per cow per day. Average production of milk per cow was 12.5 liters. The estimated Benefit Cost Ratio (BCR) was 2.17 that is dairy farmers earned Tk. 2.17 investing one taka in dairy farming.Int. J. Agril. Res. Innov. Tech. 12(1): 182-187, June 2022